Studi Deskriptif Penggunaan Software IKMS® dalam Perencanaan Program Bimbingan dan Konseling - Prilintia, Unik; Anni, Catharina Tri (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This study was conducted based on the phenomenon that occurs in Pemalang in the used of software IKMS® for planning program. The purpose of this study is to determine the description of planning BK program and the use of softwareIKMS® in SMA Negeri Pemalang. This study used qualitative research with descriptive design. This study involved counselor as the main data source and school personnel as supporting data.  The technique of collecting data used interview, check list, and documentation. The technique validity of data used triangulation source. The analysis of the data used the data display, data reduction, triangulation and verification. The result is implementation of need assessment, determination of data interpretation, determination of priority needs, goal setting program, determination of the procedure program, and evaluation planning is good. The obstacle of the using IKMS® softwarewas complicated data processed. The advantage of the using IKMS® program was more efficient because it did not need much time to analyzing data. The deficiency of the using of IKMS® program was the counselor is uncreative in making programs. From the result and discussion can be concluded that according to the councelor to use of softwareIKMS® was less effective in the planning BK programs.